(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The purpose of the study is to explore the role of technical and non-technical skills of accountants practicing the accounting profession in Iraq in creating and stimulating innovation in the field of accounting. Relevant literature was reviewed, and a proposed theoretical framework was presented to show and test the relationship between these variables. The descriptive analytical approach was used to verify and examine the relationship between creating accounting innovation and technical and non-technical skills among accountants practicing the accounting profession in Iraq. Data were collected through a form prepared for this purpose. A questionnaire form was distributed to the study sample of 320 male and female employees working as accountants in economic units in Iraq. The study used bivariate correlation techniques and multiple regression analysis techniques to examine the proposed hypotheses. The data analysis technique used in this study was used to examine the data collection process and clarify the degree of association between the research variables. The study found that technical and non-technical skills among Iraqi accountants affect stimulating and generating innovation by improving the efficiency of preparing and analysing financial and accounting data, saving time and effort in review and audit procedures, and improving the accuracy of financial reports.